Identifikasi Gaya Belajar (Visual, Auditorial, Kinestetik) Pada Siswa MA Plus Nurul Islam Sekarbela - Awwalus Sanatil Hijriati; Dedi Riyan Rizaldi; Amrullah; Syarifah Umdah Maryam; Nilwan; Ziadatul Fatimah (Action Research Journal, 2024)
The purpose of this research is to identify the learning styles of students at MA Plus Nurul Islam Sekarbela. This research uses a descriptive quantitative research design. The research population was all class XI students at MA Plus Nurul Islam Sekarbela, with the research sample being class XI students majoring in religion. Data collection techniques use questionnaire instruments and observation sheets. The data obtained in the research was then analyzed descriptively. Based on the research that has been carried out, the results show that the percentage of students' visual, kinesthetic, and auditory learning styles at MA Plus Nurul Islam Sekarbela is 56%, 24%, and 20%. The tendency for students at MA Plus Nurul Islam Sekarbela to have the highest learning style is the visual learning style.